Ultrasound-Guided Breath-Compensation in Single-Element Photoacoustic Imaging for Three-Dimensional Whole-Body Images of Mice - Lee, Haeni; Han, Seongyi; Park, Sinyoung; Cho, Seonghee; Yoo, Jinwoo; Kim, Chulhong; Kim, Jeesu (Frontiers in Physics, 2022)
Photoacoustic macroscopy is advantageous for analyzing functional information at molecular in vivo in the whole body of small animals. However, mechanical scanning typically involved in acquiring the data results in a long acquisition time, leading to breathing-related artifacts in the depth direction. Thus, the acquired three-dimensional data cannot be analyzed and visualized using two-dimensional projection rendering techniques unless the respiratory distortions are minimized. In this study, we present an ultrasound-guided breath-compensation method for the three-dimensional data of photoacoustic macroscopy to facilitate visualization and analysis in the depth direction. We first acquire photoacoustic and ultrasound data of the whole body of small animals in vivo. We then compensate the distorted skin layers in ultrasound data, which are easy to distinguish. The found distortion parameters are then applied to the corresponding photoacoustic data to compensate for the motion. We successfully applied the compensation method to visualize three-dimensional hemoglobin oxygen saturation in the whole body of mice in vivo by using multispectral photoacoustic data. The resulting three-dimensional images show that the developed methodology holds great potential for its use in various biomedical studies, including monitoring drug delivery, imaging of tumors, and analysis of vasculature network.